PENGARUH NILAI TUKAR RUPIAH DAN TINGKAT INFLASI PADA JUMLAH EKSPOR NONMIGAS INDONESIA - Aljani Sarubei; Puja Saputri Tambunan; Devi Gusnayenti; Latifa Khairul Nisa Ramli; Ansofino (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the rupiah exchange rate and inflation rate on the volume of Indonesia's non-oil and gas exports. Non-oil and gas exports play an important role in promoting economic growth, expanding domestic products into international markets, and increasing foreign exchange earnings. Fluctuations in the rupiah exchange rate and changes in the inflation rate are macroeconomic factors that may affect the competitiveness of Indonesian export products in the global market. Therefore, it is necessary to examine the extent to which these variables influence the performance of Indonesia's non-oil and gas exports. This research employs a quantitative approach using secondary data obtained from official government publications during the study period. Multiple linear regression analysis is used to examine both the partial and simultaneous effects of the rupiah exchange rate and inflation rate on non-oil and gas export volumes. The results indicate that the rupiah exchange rate has a significant effect on Indonesia's non-oil and gas exports, while the inflation rate has a relatively smaller influence. Simultaneously, both the rupiah exchange rate and inflation rate significantly affect the volume of non-oil and gas exports. These findings suggest that macroeconomic stability, particularly exchange rate management and inflation control, is essential for supporting the growth and performance of Indonesia's non-oil and gas export sector.